1999
DOI: 10.1021/jm990377j
|View full text |Cite
|
Sign up to set email alerts
|

New α-Substituted Succinate-Based Hydroxamic Acids as TNFα Convertase Inhibitors

Abstract: Tumor necrosis factor alpha convertase (TACE), the enzyme responsible for the processing of pro-TNFalpha to TNFalpha, has been reported to be a metalloproteinase closely related to matrix metalloproteinases (MMPs). Current inhibitors of TACE such as succinate-based hydroxamic acids exemplified by Marimastat (TACE IC(50): 3.8 nM; blood IC(50): 7 microM) and BB1101 (TACE IC(50): 0.2 nM; blood IC(50): 2.3 microM) suffer from modest potency in blood and poor in vivo properties. The introduction of new bulky alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 41 publications
2
65
0
Order By: Relevance
“…In the present study, however, marimastat, a broadspectrum MMP inhibitor with the ability to block TACE activity, induced MSS (27). More experimental data regarding the role of sheddases in MSS are needed.…”
Section: Discussionmentioning
confidence: 56%
“…In the present study, however, marimastat, a broadspectrum MMP inhibitor with the ability to block TACE activity, induced MSS (27). More experimental data regarding the role of sheddases in MSS are needed.…”
Section: Discussionmentioning
confidence: 56%
“…BB-94, BB-1101, and GM6001 are able to broadly inhibit the MMPs; however, they have variable inhibitory effects on TACE (Barlaam et al, 1999;Skiles et al, 2004;Rosenberg et al, 2007). Additionally, in a study of lipopolysaccharide-induced inflammation in the mouse, we found differences in response to bloodbrain barrier opening between BB-1101 and BB-94 .…”
Section: Discussionmentioning
confidence: 79%
“…Lithiation of the tertbutyl protected bromide (5) and subsequent reaction with triisopropyl borate afforded the boronic acid 6 which was coupled to 9-bromoanthracene under Suzuki cross-coupling conditions using Pd(Ph 3 ) 4 as catalyst and benzene-EtOH-H 2 O as solvent system to give 7 in 92% yield. Finally, deprotection of 7 to yield the corresponding thiol 8 was achieved with triflic acid and TFA in thioanisole [15].…”
Section: Synthesis Of the Ligandsmentioning
confidence: 99%